Prioritizing the Mental Health and Well-Being of Healthcare Workers: An Urgent Global Public Health Priority - Søvold, Lene E.; Naslund, John A.; Kousoulis, Antonis A.; Saxena, Shekhar; Qoronfleh, M. Walid; Grobler, Christoffel; Münter, Lars (Frontiers in Public Health, 2021)
The COVID-19 pandemic has had an unprecedented impact on health systems in most countries, and in particular, on the mental health and wellbeing of health workers on the frontlines of pandemic response efforts. In this perspective article we reflect on the mental health impacts on healthcare professionals during times of crisis and other challenging working conditions against a backdrop of the current COVID-19 pandemic. First, we provide a broad overview of the elevated risk of stress, burnout, moral injury and mental health challenges among healthcare workers. Secondly, we consider how public health emergencies exacerbate these concerns, as reflected in emerging research on the negative mental health impacts of the COVID-19 pandemic on healthcare workers. Further, we consider potential approaches for overcoming these threats to mental health by exploring the value of practicing self-care strategies, evidence-based approaches and interventions to help protect the mental health and wellbeing of the healthcare workforce and organizational measures to support health and wellbeing of care providers. Lastly, we highlight systemic changes to empower healthcare workers and protect their mental health and wellbeing in the long run, and propose policy recommendations to guide healthcare leaders and health systems in this endeavor. This perspective article acknowledges the stressors, burdens and psychological needs of the healthcare workforce across health systems and disciplines, and calls for renewed efforts to mitigate these challenges among those working on the frontlines during public health emergencies such as the COVID-19 pandemic.